Accurate predictions for optimum design of a T-shaped fin under an actual wet load condition. (October 2017) - Hazarika, Saheera Azmi; Bhanja, Dipankar; Nath, Sujit; Kundu, Balaram
Highlights: T-shaped wet fin with variable thermophysical parameters. Temperature dependent thermal conductivity and heat transfer coefficient. Three analytical techniques, VIM, DTM and ADM are adopted. Efficiency and optimisation analysis are carried out. Multivariable optimisation is studied. Abstract: An effort is made to develop an analytical model for predicting the thermal performance and optimum design parameters of a wet T-shaped fin by considering variable thermal conductivity of the fin material and variable convective heat transfer coefficient. The temperature distribution is obtained by solving the highly non-linear governing equations by employing three different analytical techniques, namely Variational Iteration Method, Adomian Decomposition Method and Differential Transform Method, and validated by that obtained from the Finite Difference Scheme. The optimisation analysis is carried out by employing the Lagrange multiplier technique. A complete multivariable geometric optimisation is executed, where all the geometric parameters are varied simultaneously to establish the optimum condition. Furthermore, the analysis is done for both insulated and convective fin tip conditions and a comparative analysis on the temperature distribution, fin performance and optimum design parameters is presented between these two cases.